St. Augustinegrass accessions planted in northern, central and southern Italy: Growth and morphological traits during establishment - Caturegli, Lisa; Ramazani, Rokhsareh; Volterrani, Marco; Grossi, Nicola; Magni, Simone; Macolino, Stefano; Pornaro, Cristina; La Bella, Salvatore; Tuttolomondo, Teresa; Minelli, Alberto; Gaetani, Monica (Italian Journal of Agronomy, 2018)
The use of warm season turfgrasses is a consolidated trend in the climatic transition zone of Mediterranean countries, in particular St. Augustinegrass (Stenotaphrum secundatum (Walt.) Kuntze) begins to be widespread in warm coastal areas. However, little is known about the performance of the different cultivars of this species in southern Europe. In 2016-2017 a trial was carried out in three locations in Italy, Padova, Pisa, and Palermo, located in the north, center and south of the country respectively. Four cultivars (Floratine, Captiva, Sapphire, Palmetto) and five ecotypes (CeRTES 201, CeRTES 202, CeRTES 203, CeRTES 204, CeRTES 205) were compared in terms of their growth characteristics and morphological traits during establishment. The results highlighted that stolon growth was significantly affected by the location, as well as green colour retention. Stolon growth rate, internode length and internode volume and turf quality were, however, significantly determined by the accession effect. The quality of the ecotypes was also in some cases comparable to that of the cultivars. In Padova, winterkill occurred in most of the accessions, while in Pisa and Palermo, all the entries survived. In conclusion, St. Augustinegrass is suitable for turf use in the central and southern coastal area of Italy.